The Correlation Between Maternal Knowledge and Stunting Prevention Behaviour on Toddlers in the Working Area of Blud UPT Puskesmas Pahandut Palangka Raya - Alma Adystia Elva; Melisa Frisilia; Stefanicia Stefanicia (Universitas Ibn Khaldun Bogor, 2026)
Stunting is a disorder that affects the growth and development of toddlers, characterised by the child's length or height not being commensurate with that of the same age. The existence of mothers of toddlers who do not understand how to prevent stunting, especially in terms of food processing, meeting nutritional needs, and the importance of monitoring child growth and development, will affect the incidence of stunting. Objective: This research was conducted to determine the relationship between mothers' knowledge and stunting prevention behaviours in toddlers. Method: The research method used was quantitative with a correlational study design and a cross-sectional design. The sample in this study consisted of 45 mothers of toddlers selected using purposive sampling techniques. The analysis performed was univariate and bivariate using Spearman's rank test. Result: This research showed the results of the Spearman's rank test, obtained (p = 0.003 <α = 0.05). This means there was a correlation between maternal knowledge and stunting prevention behaviour on toddlers in the BLUD UPT Puskesmas Palangka Raya working area. Conclusion: Mothers with a basic understanding of stunting tend to have implemented most stunting prevention practices, such as exclusive breastfeeding, appropriate complementary feeding, and growth monitoring in toddlers, although not yet optimal. Therefore, efforts to reduce the prevalence of stunting through primary prevention must be further enhanced by optimising health promotion so that mothers gain a deeper understanding and broader knowledge of stunting and implement preventive behaviour appropriately.